Prescription errors and administration of injectable antimicrobials in a public hospital - Ionara Vieira Rocha Da Mota; Paulo Henrique Ribeiro Fernandes Almeida; Lucas Brasileiro Lemos; Mario Borges Rosa; Gisele Da Silveira Lemos (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
To analyze the errors of prescription and administration of antimicrobials powder for solution for injection in a public hospital. This is a cross-sectional study carried out in a public hospital, in which antimicrobials prescriptions and administrations were analyzed for patients admitted to the Intensive Care Unit (ICU) and Medical Clinic (CM) from November 2015 to February 2016. The tabulation and data analysis were done in Epidata software version 3.1 of 2008 and IBM Statistical Package for the Social Sciences (SPSS). In the statistical analysis, chi-square tests or Fisher's exact test were applied when necessary. The level of significance was 5%. Among the statistically significant results, the following are the errors related to medical prescription with the variables: age at 57% and medical specialty at 67%, both at the ICU; bed with 30% and hospitalization unit with 37%, both in CM. In the administration of antimicrobials, statistically significant differences were observed only in the failure to identify the patient (30% in CM). Regarding the use of antimicrobials, Cefepime was the most prescribed with 65.1%. In view of these aspects, it is extremely important that errors arising from an incomplete and misleading prescribing are identified, to propose improvements in the medication system, in order to prevent errors, and to promote a more rational antibiotic therapy, avoiding infections.